the correlation between health behavior in the elderly and public policy, nursing function and health education - murwani, arita (Jurnal Formil (Forum Ilmiah) Kesmas Respati, 2020)
Population projection data in Indonesia in 2017 says that the elderly population is 23.660.000 people. Yogyakarta has the highest number of elderly, especially those domiciled in Sleman Regency with a total of about 105.955 people. Health behaviors in the elderly can be influenced by public policy, nursing functions, and health education. To find out the correlation between health behaviors in the elderly and public policy, nursing functions, and health education. This study uses a cross-sectional design with a quantitative research type. This research used the survey method with a questionnaire sheet as a research instrument and then the data will be processed using Stata test. Analysis of data conducted with chi-square analysis. The technique used is purposive sampling due to sampling with certain criteria. The criteria of this study include elderly who come to the health center to conduct examinations, have families, and live in the working area of Sleman District health center. The research will take place from March 2020 until completion. The elderly who were domiciled in the working area of Sleman District health center became the population in this study as many as 103.686 elderly.There is a correlation between public policy and elderly health behavior with a Pearson chi-square value of 0,472. There is a correlation nursing function with elderly health behavior with a Pearson Chi-Square value of 0,210. There is a correlation between health education and elderly health behavior, with Pearson Chi-Square value -0,210.Conclusion: There is a significant correlation between health behaviors in the elderly and public policy, nursing function, and health education.